2023
DOI: 10.15252/emmm.202216235
|View full text |Cite
|
Sign up to set email alerts
|

Thioparib inhibits homologous recombination repair, activates the type I IFN response, and overcomes olaparib resistance

Abstract: Poly‐ADP‐ribose polymerase (PARP) inhibitors (PARPi) have shown great promise for treating BRCA‐deficient tumors. However, over 40% of BRCA‐deficient patients fail to respond to PARPi. Here, we report that thioparib, a next‐generation PARPi with high affinity against multiple PARPs, including PARP1, PARP2, and PARP7, displays high antitumor activities against PARPi‐sensitive and ‐resistant cells with homologous recombination (HR) deficiency both in vitro and in vivo. Thioparib treatment elicited PARP1‐dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…IC 50 values of PARPs were obtained from histone-based (a) or biotinylated NAD + -based (b) luminescence assays. c Data from ref …”
Section: Resultsmentioning
confidence: 99%
“…IC 50 values of PARPs were obtained from histone-based (a) or biotinylated NAD + -based (b) luminescence assays. c Data from ref …”
Section: Resultsmentioning
confidence: 99%
“…Especially, it was observed that RBN2397 displayed an enhanced antitumor activity when dosing to the mice bearing PARP-1/2 KO CT-26 tumor cells . Furthermore, thioparib having PARP-1/2/7 inhibitory activity demonstrated high in vivo antitumor activity as well . Therefore, Cpd36 that embraced strong inhibition toward PARP-1/2/7 simultaneously was expected to produce beneficial antitumor effects.…”
Section: Resultsmentioning
confidence: 99%
“…42 Furthermore, thioparib having PARP-1/2/7 inhibitory activity demonstrated high in vivo antitumor activity as well. 40 Therefore, Cpd36 that embraced strong inhibition toward PARP-1/2/7 simultaneously was expected to produce beneficial antitumor effects.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations